2011
DOI: 10.1002/app.33585
|View full text |Cite
|
Sign up to set email alerts
|

Increased onset temperature of expansion in thermally expandable microspheres through combination of crosslinking agents

Abstract: Free-radical suspension polymerization was used to synthesize thermally expandable microspheres (TEMS) in which a poly(acrylonitrile-co-methacrylonitrile) shell encapsulates isooctane. TEMS were prepared with 1,4-butanediol dimethacrylate (BDDMA), in combination with 1,4-butanediol divinyl ether (BDDVE), diallyl carbonate (DAC), or allyl methacrylate, as crosslinkers. It was found that a significant increase in the onset temperature of expansion (T start ) could be obtained when a combination of BDDMA and BDDV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…Kawaguchi and coworkers prepared TEPMs consisting of an acrylonitrile (AN), methyacrylonitrile (MAN), and (meth)acrylic ester copolymer shell and investigated the effects of the chemical structure and viscoelastic properties of the polymer shell on the thermal and expansion properties of the TEPMs. Jonsson and coworkers synthesized AN–MAN copolymer microspheres by in situ suspension polymerization and investigated the monomer feed ratio, polymerization temperature, structure of the blowing agent, crosslinking agent type, and content on the expansion properties of the microspheres. They found that an initial AN–MAN feed ratio between 0.15 and 0.90 resulted in core–shell particles with encapsulated hydrocarbon when the polymerizations were carried out at 62 °C, whereas a much narrower span for the AN–MAN feed ratio (0.5–0.85) yielded particles with encapsulated hydrocarbon during polymerization at 80 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Kawaguchi and coworkers prepared TEPMs consisting of an acrylonitrile (AN), methyacrylonitrile (MAN), and (meth)acrylic ester copolymer shell and investigated the effects of the chemical structure and viscoelastic properties of the polymer shell on the thermal and expansion properties of the TEPMs. Jonsson and coworkers synthesized AN–MAN copolymer microspheres by in situ suspension polymerization and investigated the monomer feed ratio, polymerization temperature, structure of the blowing agent, crosslinking agent type, and content on the expansion properties of the microspheres. They found that an initial AN–MAN feed ratio between 0.15 and 0.90 resulted in core–shell particles with encapsulated hydrocarbon when the polymerizations were carried out at 62 °C, whereas a much narrower span for the AN–MAN feed ratio (0.5–0.85) yielded particles with encapsulated hydrocarbon during polymerization at 80 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the parameters of the polymerisation, the VNPs with various morphologies have been obtained. The particle size of 100-400 nm of the VNPs is significantly smaller than commonly reported expandable microspheres in the literature [13,14]. The structure of the VNP is of a well-defined encapsulation type with a shell thickness of 10 -50 nm.…”
Section: Methodsmentioning
confidence: 97%
“…Thermally expandable microspheres [13,14] seem to be a preferred choice for the enhancement of surface quality, but the size of the expandable microspheres, typically 10 -50 mm, is too large for ultramicrocellular or even microcellular foaming, and besides the microspheres could be expanded dozens of times in diameter compared with their original sizes after applying heat. It is desirable to fabricate ultramicrocellular polymers with a fine cell structure and good surface quality by facile and rapid processing.…”
Section: Introductionmentioning
confidence: 99%
“…They also studied the influence of monomer chemical structure on heat resistance of thermally expandable microspheres [ 23 ]. Jonsson et al have studied the effects of blowing agent structure, content and crosslinking agent structure on expansion properties of poly (AN-co-methacrylonitrile) microspheres [ 24 , 25 , 26 ]. The structure and physical properties (i.e., the boiling point and vapor pressure) of the blowing agent had a significant influence on the expansion properties of the microspheres.…”
Section: Introductionmentioning
confidence: 99%